Queueing networks : - Chao, Xiuli (Wiley, 1999)
The objective of this book is to present, in a unified framework, the latest developments in queueing networks with signals, After introducing the foundations in the first four chapters, Chapters 5 through to 8 cover a number of different queueing network models with various features. Chapters 9 to 11 focus on more fundamental structures of queueing networks and Chapter 12 presents a framework for discrete time queueing network models. The text is illustrated throughout with numerous examples. Graduate students in operations research, computer science, electrical engineering and applied mathematics will find this text accessible and invaluable. An essential reference for operation researchers and computer scientists working on queueing problems in computing, manufacturing and communications networks.